Guanylyl cyclase C signaling axis and colon cancer prevention - Pattison, Amanda M (World J Gastroenterol, 2016)
Colorectal cancer (CRC) is a major cause of cancer-related mortality and morbidity worldwide. While improved treatments have enhanced overall patient outcome, disease burden encompassing quality of life, cost of care, and patient survival has seen little benefit. Consequently, additional advances in CRC treatments remain important, with an emphasis on preventative measures. Guanylyl cyclase C (GUCY2C), a transmembrane receptor expressed on intestinal epithelial cells, plays an important role in orchestrating intestinal homeostatic mechanisms. These effects are mediated by the endogenous hormones guanylin (GUCA2A) and uroguanylin (GUCA2B), which bind and activate GUCY2C to regulate proliferation, metabolism and barrier function in intestine. Recent studies have demonstrated a link between GUCY2C silencing and intestinal dysfunction, including tumorigenesis. Indeed, GUCY2C silencing by the near universal loss of its paracrine hormone ligands increases colon cancer susceptibility in animals and humans. GUCY2C’s role as a tumor suppressor has opened the door to a new paradigm for CRC prevention by hormone replacement therapy using synthetic hormone analogs, such as the FDA-approved oral GUCY2C ligand linaclotide (Linzess™). Here we review the known contributions of the GUCY2C signaling axis to CRC, and relate them to a novel clinical strategy targeting tumor chemoprevention.